The Effect of Online Sales on Consumer Purchase Interest in Perbaungan City - Liska Febrianti; Siti Aisyah (Journal of Indonesian Management, 2022)
In today's digital era, everything can be done online as well as shopping. Recently, consumer buying interest in online shopping has greatly increased, especially during the Covid-19 period when there was a government regulation regarding self-isolation. Of course this is a strong enough reason for the development of online sales. This study describes how the influence of online sales on consumer buying interest in the city of Perbaungan. This research uses descriptive quantitative and qualitative descriptive methods by distributing questions via google forms given to the people of Perbaungan city who have made online purchases. From the analysis of data with 100 respondents, it can be seen that online sales greatly affect consumer buying interest in an item on the grounds that purchases are made easier and cheaper than direct purchases to stores.